2018
DOI: 10.2147/ijn.s176287
|View full text |Cite
|
Sign up to set email alerts
|

CAIX aptamer-functionalized targeted nanobubbles for ultrasound molecular imaging of various tumors

Abstract: PurposeTargeted nanobubbles can penetrate the tumor vasculature and achieve ultrasound molecular imaging (USMI) of tumor parenchymal cells. However, most targeted nanobubbles only achieve USMI of tumor parenchymal cells from one organ, and their distribution, loading ability, and binding ability in tumors are not clear. Therefore, targeted nanobubbles loaded with carbonic anhydrase IX (CAIX) aptamer were fabricated for USMI of various tumors, and the morphological basis of USMI with targeted nanobubbles was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…Liposomes have the advantages of good biocompatibility, simple preparation process, fewer toxic and side effects, and are widely used in gene transfection, drug delivery and in vivo imaging [19]. Our previous findings and other related studies have shown that nanobubbles with a lipid shell have the characteristics of entering tumor tissues through tumor blood vessels and concentrating therein for a long time [20]. At the same time, ultrasound targeted nanobubble destruction (UTND) provides an effective way to direct drugs to specific parts of the body; effectively increasing the content of the drug in the tumor area and reducing potential side effects, thereby contributing effectively to the treatment of the tumors.…”
Section: Introductionmentioning
confidence: 81%
“…Liposomes have the advantages of good biocompatibility, simple preparation process, fewer toxic and side effects, and are widely used in gene transfection, drug delivery and in vivo imaging [19]. Our previous findings and other related studies have shown that nanobubbles with a lipid shell have the characteristics of entering tumor tissues through tumor blood vessels and concentrating therein for a long time [20]. At the same time, ultrasound targeted nanobubble destruction (UTND) provides an effective way to direct drugs to specific parts of the body; effectively increasing the content of the drug in the tumor area and reducing potential side effects, thereby contributing effectively to the treatment of the tumors.…”
Section: Introductionmentioning
confidence: 81%
“…Liposomes have the advantages of good biocompatibility, a simple preparation process, and fewer toxic effects and side effects and are widely used in gene transfection, drug delivery and in vivo imaging [21]. Our previous ndings and other related studies have shown that nanobubbles with a lipid shell can enter tumour tissues through tumour blood vessels and concentrate therein for a long period of time [22]. Moreover, ultrasound-targeted nanobubble destruction (UTND) provides an effective way to direct drugs to speci c parts of the body, effectively increasing the drug content in the tumour area and reducing potential side effects, thereby contributing effectively to the treatment of tumours.…”
Section: Introductionmentioning
confidence: 89%
“…Another diagnostic approach employs ultrasound molecular imaging (USMI), using CAIX-targeted bubbles, allowing the detection of masses that express the marker. Facility, accessibility and innocuity are solid arguments for this technique [ 41 ]. Table 2 summarizes the evidence on the clinical value of CAIX targeting in molecular imaging.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Zhu et al described a new USMI contrast product: CAIX aptamer-functionalized targeted nanobubbles [ 41 ]. As seen above, CAIX may be expressed by many different malignancies and it is a trans-membranous protein.…”
Section: Evidence Synthesismentioning
confidence: 99%